Analisis Dan Perencanaan Strategi Sistem Informasi Menggunakan TOGAF ADM Di DISDUKCAPIL Halmahera Utara - Sandy Anu (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Abstrack The application of Information Technology has expanded to various fields of human life, including in the field of government. The Department of Population and Civil Registration of North Halmahera Regency (DISDUKCAPIL HALUT) is a government institute that is engaged in population administration affairs. As technology develops and the need for population administration continues to increase all the time, it requires the Department of Population and Civil Registration of North Halmahera Regency to evaluate the technology and information systems currently in use in order to improve services to the community in North Halmahera Regency. To evaluate technology and information systems, researchers use the TOGAF ADM framework. The purpose of this study is to provide information technology and systems proposals in the form of information systems strategy planning blueprints.